Teaching together in entrepreneurship education: live case method - Ilonen Sanna; Hytti Ulla (Edward Elgar Publishing, 2022)
Case method is widely used in business and entrepreneurship education. Different from the traditional textbook cases that are based on an analysis of history, live case method is receiving increased attention. We suggest that venture creation courses are a form of live case method where students can learn from their own venture creation processes. As extant entrepreneurship education research has mainly focused on students’ perspectives, we address the omission of sharing entrepreneurship educators’ perspectives by focusing on team teaching in a live case situation. Team teaching has not been previously addressed in entrepreneurship education research despite several benefits it can bring. This chapter presents benefits and challenges of interactive team teaching based on the literature and interviews with team teachers in a Finnish start-up course. The chapter targets entrepreneurship educators and scholars interested in and/or encouraged towards team teaching in higher education. We provide concrete advice for educators on how to enhance team teaching.
Reframing the Case Method in Entrepreneurship Education: Cases from the Nordic Countries